Rocking sensitivity of a dual‐block stack ‐ Numerical simulation and experimental evidence - Čeh, Nina; Jelenić, Gordan; Bićanić, Nenad (Earthquake engineering & structural dynamics, 2024)
Historic monuments, drywall structures, and graphite blocks in AGR nuclear power plants are block‐like structures that have to withstand rocking when subject to seismic excitation of their base, which can lead to overturning of some of their components and results in the collapse of the whole structure. We revisit the known nonlinear equations of motion for a dual‐block stack and present the conditions for transition between the eight possible rocking configurations (due to initiation of rocking, opening of new contacts, and collisions between blocks). An algorithm for the numerical simulation of rocking of the dual‐block stack is developed using the Newmark integration method, the Newton‐Raphson iteration method, and a novel contact detection and resolution procedure. The algorithm is used to evaluate rocking stability of five dual‐block stacks, one of which is compared to the results available in the literature. In parallel, a novel experimental program is designed and implemented, to validate the numerically obtained results using a shaking table. While most of the excitation conditions leading to stable rocking and limit values leading to overturning have been successfully validated, some discrepancies between the numerically and experimentally obtained results still exist and point to the need for improvement of the algorithm used, possibly through a more realistic energy‐loss mechanism. Most importantly, we have confirmed the known theoretical prediction that splitting a single block into two half‐size blocks benefits its rocking stability.